Corporate social responsibility for agricultural Development - a way forward - Balasubramani, N (Journal of Agricultural Extension Management, 2018)
A huge investment is required to address the current challenges of agriculture. These challenges provide space for a pluralistic eco-system to involve various players. The Corporate sector is one of the important players in the current policy initiative to leverage Corporate Social Responsibility (CSR) funds for agricultural development. However, a very small amount of CSR fund has been spent in the agricultural sector by the companies though there is huge potential for investment in the sector. Agriculture is yet to attract the attention of India’s CSR. Countries that had relatively high Agriculture growth, saw substantial reduction in poverty. Hence, if the Corporates allocate more fund under CSR in agriculture, many challenges of the farm sector can be addressed. Corporates who have invested in Agriculture as part of CSR activities have seen a significant improvement in terms of adoption of improved agriculture practices, conservation of natural resources, reduction in external inputs and cost of cultivation, etc., in their project areas. The emphasis of CSR in the Agriculture sector needs to be in the areas of environmental sustainability, natural resource management, innovation and technology led development, social development, entrepreneurship development, livestock development, market development, farm advisory services, etc. In order to promote CSR activities in Agriculture, it is suggested to have a Special Purpose Vehicle (SPV), steering committee having broad based representation of various stakeholders, proper monitoring system at various levels, etc